Kaposi's Sarcoma-Associated Herpesvirus Deregulates Host Cellular Replication during Lytic Reactivation by Disrupting the MCM Complex through ORF59 - Strahan, Roxanne (J Virol, 2018)
Minichromosome maintenance proteins (MCMs) play an important role in DNA replication by binding to the origins as helicase and recruiting polymerases for DNA synthesis. During the S phase, MCM complex is loaded to limit DNA replication once per cell cycle. We identified MCMs as ORF59 binding partners in our protein pulldown assays, which led us to hypothesize that this interaction influences DNA replication. ORF59's interactions with MCMs were confirmed in both endogenous and overexpression systems, which showed its association with MCM3, MCM4, MCM5, and MCM6. Interestingly, MCM6 interacted with both the N- and C-terminal domains of ORF59, and its depletion in BCBL-1 and BC3 cells led to an increase in viral genome copies, viral late gene transcripts, and virion production compared to the control cells following reactivation. MCMs perform their function by loading onto the replication competent DNA, and one means of regulating chromatin loading/unloading, in addition to enzymatic activity of the MCM complex, is by posttranslational modifications, including phosphorylation of these factors. Interestingly, a hypophosphorylated form of MCM3, which is associated with reduced loading onto the chromatin, was detected during lytic reactivation and correlated with its inability to associate with histones in reactivated cells. Additionally, chromatin immunoprecipitation showed lower levels of MCM3 and MCM4 association at cellular origins of replication and decreased levels of cellular DNA synthesis in cells undergoing reactivation. Taken together, these findings suggest a mechanism in which KSHV ORF59 disrupts the assembly and functions of MCM complex to stall cellular DNA replication and promote viral replication. IMPORTANCE KSHV is the causative agent of various lethal malignancies affecting immunocompromised individuals. Both lytic and latent phases of the viral life cycle contribute to the progression of these cancers. A better understanding of how viral proteins disrupt functions of a normal healthy cell to cause oncogenesis is warranted. One crucial lytic protein produced early during lytic reactivation is the multifunctional ORF59. In this report, we elucidated an important role of ORF59 in manipulating the cellular environment conducive for viral DNA replication by deregulating the normal functions of the host MCM proteins. ORF59 binds to specific MCMs and sequesters them away from replication origins in order to sabotage cellular DNA replication. Blocking cellular DNA replication ensures that cellular resources are utilized for transcription and replication of viral DNA.